2013
DOI: 10.3748/wjg.v19.i12.1861
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms, prevention and clinical implications of nonsteroidal anti-inflammatory drug-enteropathy

Abstract: This article reviews the latest developments in understanding the pathogenesis, detection and treatment of small intestinal damage and bleeding caused by nonsteroidal anti-inflammatory drugs (NSAIDs). With improvements in the detection of NSAID-induced damage in the small intestine, it is now clear that this injury and the associated bleeding occurs more frequently than that occurring in the stomach and duodenum, and can also be regarded as more dangerous. However, there are no proven-effective therapies for N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
149
0
28

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 181 publications
(271 reference statements)
3
149
0
28
Order By: Relevance
“…The adverse drug reactions in the duodenum, jejunum, and ileum are collectively termed enteropathy. Obvious small intestinal damage and bleeding occur in 70% of chronic NSAID users, although most patients do not show obvious clinical symptoms [2] . Some reports have shown an association between NSAID use and significant damage to the more distal regions of the small intestine [3] .…”
Section: Introductionmentioning
confidence: 99%
“…The adverse drug reactions in the duodenum, jejunum, and ileum are collectively termed enteropathy. Obvious small intestinal damage and bleeding occur in 70% of chronic NSAID users, although most patients do not show obvious clinical symptoms [2] . Some reports have shown an association between NSAID use and significant damage to the more distal regions of the small intestine [3] .…”
Section: Introductionmentioning
confidence: 99%
“…Although an abundance of evidence exists to suggest that bacteria contribute to the development of NSAID enteropathy, whether the bacteria directly initiate the damage once the intestine has been rendered susceptible to injury through inhibition of mucosal prostaglandin synthesis or whether bacteria exacerbate pre-existing tissue injury and impede repair remains unclear [1,2]. An additional layer of complexity in determining the role of bacteria in NSAID enteropathy is that the intestinal microbiota, enterohepatic circulation, and bile are all closely interrelated.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Although there are drugs available for preventing the upper GI tract adverse effects of NSAIDs (inhibitors of gastric acid secretion), no measures have been identified that have been proven to be effective at preventing the small intestinal injury caused by these drugs [1,4,5]. There are also no proven-effective treatments for NSAID enteropathy once it has occurred [1,2,4]. With improved means of detection, such as video capsule endoscopy, physicians are becoming more aware that the small intestinal damage caused by NSAIDs is much more common and much more serious than previously recognized [4,[6][7][8][9][10][11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 The most significant among all of the adverse effects of these drugs include gastrointestinal (GI) ulceration and bleeding. 12,13 There are also increased risks of cardiovascular events. 14,15 Though widely used, the ulceration and bleeding caused by these drugs remain a major clinical concern.…”
Section: Non-steroidalmentioning
confidence: 99%